PRIMARY BRAIN ABSCESS BY Burkholderia cenocepacia - A RARE AND UNIQUE PRESENTATION - J K, Saravana Priya; T, Vidhya; Shekar, Nagarathna; HB, Veena Kumari (PERDOSSI (Perhimpunan Dokter Spesialis Saraf Indonesia Cabang Malang) - Indonesian Neurological Association Branch of Malang cooperated with Neurology Residency Program, Faculty of Medicine Brawijaya University, Malang, Indonesia, 2025)
Burkholderia cenocepacia, a gram-negative bacillus belonging to the Burkholderia cepacia complex (BCC), is an opportunistic pathogen known for its high intrinsic antibiotic resistance and ability to cause life-threatening infections in immunocompromised individuals. While this organism is commonly encountered in hospital-acquired infections, particularly in patients with cystic fibrosis and chronic granulomatous disease, cases of community-acquired infections are exceedingly rare. This case report presents a unique community-acquired Burkholderia cenocepacia brain abscess in a chronic alcoholic and diabetic patient, highlighting the interplay between immunosuppression, occupational exposure, and the emergence of rare infections. A 35-year-old male, working as a painter, presented with headache and generalized tonic-clonic seizures. He had a history of chronic alcohol consumption and diabetes, both of which compromise immune function and increase susceptibility to infections. Advanced imaging revealed chronic subdural hematoma (SDH) at the right convexity, necessitating surgical intervention. A right fronto-parietal craniotomy was performed with evacuation of empyema and augmentive duroplasty, followed by placement of the bone flap in the abdomen. Laboratory findings demonstrated anemia, neutrophilia, and lymphopenia, suggestive of an ongoing systemic infection. Microbiological analysis, including MALDI-TOF MS, confirmed Burkholderia cenocepacia as the causative organism. Antibiotic susceptibility testing revealed sensitivity to ceftazidime, cotrimoxazole, meropenem, minocycline, and levofloxacin, with ceftazidime selected as the primary treatment. Targeted intravenous ceftazidime therapy at a dosage of 2 grams every 6 hours for four weeks resulted in significant clinical improvement, marked by resolution of headache and seizures, improved hematological parameters, and a follow-up CT scan showing no new abscess formation. The absence of adverse effects and excellent treatment adherence reinforced the efficacy of the antibiotic regimen. This case underscores the critical role of early recognition, advanced imaging techniques, and culture-based antibiotic selection in managing rare brain abscesses. The immunocompromised state induced by chronic alcohol consumption and diabetes likely predisposed the patient to this atypical central nervous system infection, further compounded by occupational exposure and smoking history. The findings highlight the importance of multidisciplinary management in treating such challenging infections, with prompt neurosurgical intervention and tailored antimicrobial therapy proving essential for successful outcomes. This report adds to existing literature by documenting the first-known community-acquired Burkholderia cenocepacia brain abscess in an immunocompromised adult. It emphasizes the need for heightened clinical awareness, individualized therapeutic approaches, and stringent infection control strategies in the management of rare pathogens in non-hospital settings.